A catalog of Pelecorhynchidae (Diptera: Tabanomorpha) from Chile - González, Christian R; Elgueta, Mario (Zootaxa, 2020)
A catalog of the Pelecorhynchidae from Chile is provided. We presented all valid names and synonyms for the 9 species and 1 genus for the country, including information about name, author, year of publication, page number, type species, type locality and references. The geographical distribution of the species known from Chile was compiled from bibliographic data and revised collections.